(Not) talking about politics on Facebook: the case of Croatian young adults. (2016) - Vesnić-Alujević, Lucia
In the era of declined public trust in democratic institutions, the emergence of social media renewed hopes for citizens' firmer inclusion and engagement in politics. This study explores young adults' online political engagement in a new European Union member state - Croatia. This case is particularly important as it deals with a 'newly' democratic country that faces low levels of trust in politicians. Starting with their levels of offline participation, I examined levels of online political participation and the connection and interaction between them. An online survey was supplemented with a limited number of in-depth interviews to further examine the underlying reasons for certain opinions and attitudes. The results show that social media are a good tool for boosting political participation among young Croatian citizens and influencing voters' opinions, despite the fact that one of the main characteristics of this type of communication remains clicktivism.